Red sparrow eaudiobook Red sparrow series, book 1. - Matthews, Jason (Red Sparrow, 2014)
After a decorated CIA career spanning 30 years, Jason Matthews makes his fiction debut with the espionage thriller Red Sparrow. Russian intelligence officer Dominika Egorova is a "sparrow," trained in both spy games and seduction. Her target is CIA operative Nathaniel Nash, and the two have an instant, passionate—and ultimately deadly—connection.